FORENSIC VALUATION, ITS PLACE IN THE TYPOLOGICAL NOMENCLATURE OF FORENSIC INVESTIGATIONS CONDUCTED BY FORENSIC SCIENCE ORGANIZATIONS OF THE RUSSIAN MINISTRY OF JUSTICE, AND THE SCOPE OF EXPERT COMPETENCE IN THE DELIVERY OF FORENSIC VALUATION SERVICES - K. Petrov (Теория и практика судебной экспертизы, 2015)
The author discusses the potential for treating forensic valuation as a separate type of forensic inquiry, its place in the structural framework of forensic services, and the scope of expert competence fulfilled by forensic valuation analysts.